Marketing Effectiveness Through Instagram in SME Rw 05 Made Village Surabaya - Riko Setya Wijaya; Zumrotul Fitriyah (Nusantara Science and Technology Proceedings, 2021)
Developments in this new normal era, namely during the COVID-19 virus pandemic, one by one modern retail markets, large, micro, to small began to experience a decline in income. in this new normal. the impact of the rapid development of technology in this new normal era is the rise of digital marketing, especially Instagram. This study aims to analyze the effectiveness of promotions using Instagram media. Promotional effectiveness is measured by the AIDA concept (Attention, Interest, Desire, Action). The sample in this study was 35 active Instagram account owners who followed at least one account. Data analysis method using validity and reliability test of data and one-sample t-test. The results of the study reveal that by using Instagram, SME actors can market industrial products to increase economic needs in this new normal period, especially SME actors in RW 05 Made Surabaya. resulting industry.